Vitamin D3 actions on astrocyte cells: A target for therapeutic strategy in Parkinson's disease?. (10th January 2023) - de Siqueira, Erlânia Alves; Magalhães, Emanuel Paula; de Menezes, Ramon Róseo Paula Pessoa Bezerra; Sampaio, Tiago Lima; Lima, Danya Bandeira; da Silva Martins, Conceição; Neves, Kelly Rose Tavares; de Castro Brito, Gerly Anne; Martins, Alice Maria Costa; de Barros Viana, Glauce Socorro
Highlights: Rotenone induces mitochondria dysfunction in astrocytes; Rotenone increases NF-kB expression in astrocytes; Rotenone also increases Nrf2 expression in astrocytes; These effects are possibly a consequence of the rotenone-induced oxidative stress; Vitamin D improves cell viability and prevents all these rotenone effects, pointing to its neuroprotective actions and possible benefits in neurodegenerative diseases as PD. Abstract: Parkinson's disease (PD) is a neurodegenerative disease characterized by the loss of dopaminergic cells in the substantia nigra pars compacta. PD patients' brains show neuroinflammation, oxidative stress, and mitochondrial dysfunction. The present study aims to evaluate the neuroprotective activity of VD3 on astrocytes after their exposure to rotenone (ROT) a natural pesticide known to exhibit neurotoxic potential via the inhibition of mitochondrial complex I. Cell viability parameters were evaluated by the MTT test and staining with 7-AAD in cultures of astrocytes treated and untreated with VD3 (0.1, 0.5, and 1.0 ng/mL) and/or ROT (10 µg/mL or 5 µg/mL), and the cytoplasmic production of ROS and the cell death profile were measured by flow cytometry. Glutathione accumulation and ultrastructural changes were evaluated and immunocytochemistry assays for NF-kB and Nrf2 were also carried out. The results showed that VD3 improved the viability of cells previously treated with VD3 and then exposed to ROT, reducing the occurrence of necrotic and apoptotic events. Furthermore, cells exposed to ROT showed increased production of ROS, which decreased significantly with previous treatment with VD3. Importantly, the decrease by ROT in the mitochondrial transmembrane potential was significantly prevented after treating cells with VD3, especially at a concentration of 1 ng/mL. Therefore, treatment with VD3 protected astrocytes from damage caused by ROT, decreasing oxidative stress, decreasing NF-kB and Nrf2 expressions, and improving mitochondrial function. However, further investigation is needed regarding the participation and mechanism of action of VD3 in this cellular model of PD focusing on the crosstalk between Nrf2 and NF-kB.